How Implicit–Explicit Consistency of the Intelligence Self–Concept Moderates Reactions to Performance Feedback. Issue 3 (May 2013) - Gerstenberg, Friederike X. R.; Imhoff, Roland; Banse, Rainer; Altstötter–Gleich, Christine; Zinkernagel, Axel; Schmitt, Manfred
At present, it is not well understood which individual characteristics determine whether individuals will benefit or suffer from feedback about suboptimal performance. Three separate studies tested the idea that individuals' reactions to (neutral versus negative; positive versus negative) feedback as either improving or deteriorating performance in intelligence tests depended on their explicit and implicit self–concept of intelligence (eSCI and iSCI). In all studies (Study 1, N = 177; Study 2, N = 165; Study 3, N = 132), persons with low eSCI/high iSCI showed a boost in performance after negative feedback, whereas persons with any other combination showed a decline in performance. The studies also provide an explanation for these effects in terms of mediating mechanisms. Whereas the performance boost of individuals with low eSCI/high iSCI can be best explained by achievement–related reactance (Studies 2 and 3) and decrease in ruminative thinking (Study 3), the performance declines in the other configurations were mediated by decreased achievement motivation, increased frustration and increased outrage (Study 3). All these mediating mechanisms proved independent and incremental in a bootstrapping–based moderated meditation analysis. The results are discussed in light of the construct validity of our Implicit Association Test (IAT) and IATs in general. Copyright © 2013 John Wiley & Sons, Ltd.